Media Pembelajaran Training Kit Son Off Menggunakan Son Off : Uji Validitas dan Praktikalitas - Sarumaha, Ikhlas Fa'auri; Islami, Syaiful (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research is motivated by the fact that many students still have learning outcomes below the KKM in class XI TITL students of SMK Muhammadiyah 1 Padang in the subject of Electrical Lighting Installation. One of the factors that influence the low grades of students is the application of learning media that does not yet require students to play an active role in learning. Therefore, it is necessary to conduct research using learning media to achieve more effective learning so that student learning outcomes increase. The type of model used in this study is the Instructional Development Institute (IDI) model. In this IDI, the principles of a systems approach are applied which include three stages, namely discovery (define), development (develop), and evaluation (evaluate). The discovery stage (define) contains the steps of background analysis and problem identification. The second stage is the development stage (develop) which contains the preparation of the initial form (prototype) of the product and product validation. Then the third stage is the evaluation/assessment stage (evaluate) which contains the steps of testing and analyzing the results of the trial. The results of the study indicate that the developed Son Off Training Kit can improve students' understanding of the basic and practical concepts of electrical lighting installations. Based on validation tests from material and media experts, this Training Kit gets the